Effect of Social Media Marketing “Instagram” Towards Purchase Intention : Evidence From Plant-Based Milk Product “Oatside” in Indonesia - Whisnu Febriansyah; Ratna Mega Yunita; Reza Nugraha (Green Publisher Indonesia, 2024)
In the ever-evolving field of marketing, building and maintaining purchase intent remains a central theme and a significant challenge for marketers. Among various strategies em-ployed to sustain customer brand loyalty, social media marketing has emerged as a recent and effective tool. This study delves into the impact of social media marketing on the pur-chase intent of consumers, an area that is garnering growing interest from both marketing scholars and industry practitioners. The research specifically encompasses customers in Indonesia who follow